PENINGKATAN KAPASITAS PENELITI MUDA DALAM MERUMUSKAN PERTANYAAN RISET YANG NONTRIVIAL: STRATEGI UNTUK PENELITIAN YANG BERMAKNA - Abdillah, Muhammad Rasyid; Anita, Rizqa; Rizqi, Liza; Tristiyani, Tristiyani (Jurnal Pengabdian Kompetitif, 2025)
This community engagement program aimed to enhance early-career researchers’ ability to formulate nontrivial research questions—those characterized by theoretical depth and academic relevance. Conducted in collaboration with the ABC Research Institute of XYZ University (anonymous), the training integrated conceptual frameworks, case discussions, and practical exercises. Evaluation through pretest and posttest revealed a significant improvement in participants’ understanding and their ability to design meaningful research questions. These findings demonstrate that targeted interventions can strengthen research capacity and support the production of high-impact scholarly work. Keywords: Scientific journals, nontrivial research question, scientific research.